2011
DOI: 10.1142/s0218271811019712
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Processes in Black Hole-Jet Magnetospheres — Invited Review

Abstract: The environs of supermassive black holes are among the universe's most extreme phenomena. Understanding the physical processes occurring in the vicinity of black holes may provide the key to answer a number of fundamental astrophysical questions including the detectability of strong gravity effects, the formation and propagation of relativistic jets, the origin of the highest energy gamma-rays and cosmic rays, and the nature and evolution of the central engine in active galactic nuclei (AGN). As a step towards… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 225 publications
(281 reference statements)
2
58
0
Order By: Relevance
“…To illustrate the physical reason for theexistence of this factor, Broderick & Tchekhovskoy (2015) computed the divergence of the electric field in the gap. However, as the gap electric field they adopted afield determined by an expression similar to Equation (6), i.e., a value that overestimates the true field by the factor R/h (see, e.g., Blandford & Znajek 1977;Levinson & Rieger 2011;Rieger 2011, for a more accurate introduction of the electric field in the gap). Thus, the factor suggested by Broderick & Tchekhovskoy (2015) seems to be strongly overestimated.…”
Section: The Magnetospheric Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate the physical reason for theexistence of this factor, Broderick & Tchekhovskoy (2015) computed the divergence of the electric field in the gap. However, as the gap electric field they adopted afield determined by an expression similar to Equation (6), i.e., a value that overestimates the true field by the factor R/h (see, e.g., Blandford & Znajek 1977;Levinson & Rieger 2011;Rieger 2011, for a more accurate introduction of the electric field in the gap). Thus, the factor suggested by Broderick & Tchekhovskoy (2015) seems to be strongly overestimated.…”
Section: The Magnetospheric Modelmentioning
confidence: 99%
“…Finally, it has been suggested that the flares can be produced in the BH magnetosphere (Neronov & Aharonian 2007;Levinson & Rieger 2011;Rieger 2011). In this case, the production site does not move relativistically withrespect to the observer, and Equation (2) is reduced to t l > t var 0 , where l = R r g .…”
Section: Introductionmentioning
confidence: 99%
“…This scenario can explain the 2010 flare but does not provide a quantitative prediction of the light curve of the flare. Similarly, the magnetosphere model [21][22][23] can explain the hard TeV spectrum but in this case also there is no detailed quantitative predication for the VHE light curve. The work by Cui et al [24] explains the VHE gamma ray flare in an external inverse Compton model with a very wide jet.…”
Section: Introductionmentioning
confidence: 99%
“…the hadronic interaction of relativistic protons with ambient matter in the large-scale (halo-size) region ("Fermi-bubble like") [32], the integrated gammaray contribution from a supposed population of millisecond pulsars [33], or (leptonic) inverse-Compton processes with various photon fields (SSC, starlight, CMB, EBL) in the kpc-scale jet of Cen A [34,35], (iii) inner (pc-scale an below) jet models such a multiple (leptonic) SSC-emitting components moving at different angles to the line of sight [36], photo-meson (pγ) interactions of ultra-high energy protons in strong photons fields (e.g. standard disk-type) on inner jet scales [37,38,39] and elaborated lepto-hadronic variants thereof [40,41], or γ-ray induced pair-cascades in a putative dusty torus-like region [42], last not least (iv) magnetospheric scenarios based on leptonic inverse Compton processes in an under-luminous ADAF-type environment [43,44]. All of these models come with some challenges, from e.g.…”
Section: Centaurus Amentioning
confidence: 99%